Upacara Jamasan Pusakan Kanjeng Kyai Upas di Tulungagung dalam perspektif Islam - Fastrana Arya Syah Musyaffa; Lutfiah Ayundasari (Universitas Negeri Malang, 2021)
Culture is a thing related to human mind and mind. In anthropological studies, culture is considered to be an abbreviation of culture so there is no difference based on its definition. Culture is a way of life that is formed from many complex elements (religion, politics, customs, language, art, etc.) and develops in a group of people or society. Culture is often considered a legacy from generation to generation and an integral part of human beings so many people tend to consider it genetically inherited. The term culture comes from the basic word culture so that it has a connection of meaning. While Islamic culture is a concept of a culture with the entry of elements smelling of Islam. But many people are mistaken in placing a culture with Islam, so there are various public opinions that can bring down a certain culture. In writing this article, will discuss how the form of local cultural acculturation Jamasan Pusaka Kanjeng Kyai Upas with Islamic culture. Kebudayaan dan budaya merupakan hal-hal yang berkaitan dengan budi dan akal manusia. Dalam kajian Antropologi, budaya dianggap merupakan singkatan dari kebudayaan sehingga tidak ada perbedaan berdasarkan definisinya. Budaya merupakan suatu cara hidup yang terbentuk dari banyak unsur yang rumit (agama, politik, adat istiadat, bahasa, seni, dll) dan berkembang pada sebuah kelompok orang atau masyarakat. Budaya sering kali dianggap warisan dari generasi ke generasi dan bagian tak terpisahkan dari diri manusia sehingga banyak orang cenderung menganggapnya diwariskan secara genetis. Istilah kebudayaan berasal dari kata dasar budaya sehingga memiliki keterkaitan makna. Sedangkan kebudayaan Islam merupakan suatu konsep suatu budaya dengan masuknya unsur-unsur berbau Islam. Namun banyak masyarakat yang keliru dalam menempatkan sebuah budaya dengan Islam, sehingga muncul berbagai opini-opini masyarakat yang dapat menjatuhkan budaya tertentu. Dalam penulisan artikel ini, akan membahas bagaimana bentuk akulturasi budaya lokal Jamasan Pusaka Kanjeng Kyai Upas dengan kebudayaan Islam.